Renal Function Impact in the Prognostic Value of Galectin-3 in Acute Heart Failure - Caravaca Perez, Pedro; González-Juanatey, José R.; Nuche, Jorge; Matute-Blanco, Lucia; Serrano, Isabel; Martínez Selles, Manuel; Vázquez García, Rafael; Martínez Dolz, Luis; Gómez-Bueno, Manuel; Pascual Figal, Domingo; Crespo-Leiro, María G.; García-Osuna, Álvaro; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Galectin-3 (Gal-3) is an inflammatory marker associated with the development and progression of heart failure (HF). A close relationship between Gal-3 levels and renal function has been observed, but data on their interaction in patients with acute HF (AHF) are scarce. We aim to assess the prognostic relationship between renal function and Gal-3 during an AHF episode. Materials and Methods This is an observational, prospective, multicenter registry of patients hospitalized for AHF. Patients were divided into two groups according to estimated glomerular filtration rate (eGFR): preserved renal function (eGFR ≥ 60 mL/min/1.73 m2) and renal dysfunction (eGFR <60 mL/min/1.73 m2). Cox regression analysis was performed to evaluate the association between Gal-3 and 12-month mortality. Results We included 1,201 patients in whom Gal-3 values were assessed at admission. The median value of Gal-3 in our population was 23.2 ng/mL (17.3–32.1). Gal-3 showed a negative correlation with eGFR (rho = −0.51; p < 0.001). Gal-3 concentrations were associated with higher mortality risk in the multivariate analysis after adjusting for eGFR and other prognostic variables [HR = 1.010 (95%-CI: 1.001–1.018); p = 0.038]. However, the prognostic value of Gal-3 was restricted to patients with renal dysfunction [HR = 1.010 (95%-CI: 1.001–1.019), p = 0.033] with optimal cutoff point of 31.5 ng/mL, with no prognostic value in the group with preserved renal function [HR = 0.990 (95%-CI: 0.964–1.017); p = 0.472]. Conclusions Gal-3 is a marker of high mortality in patients with acute HF and renal dysfunction. Renal function influences the prognostic value of Gal-3 levels, which should be adjusted by eGFR for a correct interpretation.